2022
DOI: 10.1126/sciadv.abo3192
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive exercise-induced inflammatory response and exerkine induction in skeletal muscle of people with type 2 diabetes

Abstract: Mechanistic insights into the molecular events by which exercise enhances the skeletal muscle phenotype are lacking, particularly in the context of type 2 diabetes. Here, we unravel a fundamental role for exercise-responsive cytokines ( exerkines ) on skeletal muscle development and growth in individuals with normal glucose tolerance or type 2 diabetes. Acute exercise triggered an inflammatory response in skeletal muscle, concomitant with an infiltration of immune cells. These exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 44 publications
0
19
1
Order By: Relevance
“…Similarly, other myogenic genes such as Myogenin, MYOD, and MRF4 have been shown to be upregulated at timepoints ranging between 2 and 12 h after acute exercise in both young and old individuals, 19,38 and a decrease in the expression of MSTN, which can block muscle growth, is also commonly observed 15 . In parallel, genes involved in extracellular matrix remodeling (e.g., COL3A1, CTGF) 42 and mitochondrial biogenesis (e.g., PPARG, PPARGC1A) are also activated 14,42 along with inflammatory genes 39 . In this study, we did not observe a clear upregulation of genes involved in muscle synthesis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, other myogenic genes such as Myogenin, MYOD, and MRF4 have been shown to be upregulated at timepoints ranging between 2 and 12 h after acute exercise in both young and old individuals, 19,38 and a decrease in the expression of MSTN, which can block muscle growth, is also commonly observed 15 . In parallel, genes involved in extracellular matrix remodeling (e.g., COL3A1, CTGF) 42 and mitochondrial biogenesis (e.g., PPARG, PPARGC1A) are also activated 14,42 along with inflammatory genes 39 . In this study, we did not observe a clear upregulation of genes involved in muscle synthesis.…”
Section: Discussionmentioning
confidence: 98%
“…The response of healthy uninjured skeletal muscle to resistance exercise has been described in both animal and human models, 15,36 across genders, 37 and over the spectrum of age 38 . Models of response to an acute bout of resistance exercise demonstrate activation peaking between 2 and 8 h after exercise, although these response times depend on the specific gene of interest and can be shown to maintain elevated activation for up to 48 h after the exercise bout 19,36,39 . As such, there is large variability in gene expression response over time and across different muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Mimicking exercise in in vitro cultures utilizing EPS with primary human myotubes yields molecular responses that are relatable to in vivo responses of skeletal muscle to exercise [59; 60]. Often these studies fail to report a visually contracting phenotype or if provided, show diminutive degrees of movement likely due to the limitations of previous in vitro differentiation protocols and the use of serum [27; 28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to aberrant exercise-induced signal transduction, there is evidence that an altered transcriptional response to acute exercise may occur in metabolic disease. Pillon et al (61) demonstrated that the transcriptional response to 30 min of cycling exercise was significantly different in men with type 2 diabetes compared with those with normal glucose tolerance. Specifically, men with diabetes demonstrated enrichment of genes associated with inflammation and ECM remodeling, and reduced expression of genes associated with metabolic control (61).…”
Section: Altered Exercise-induced Gene Expression In Skeletal Musclementioning
confidence: 99%
“…Pillon et al (61) demonstrated that the transcriptional response to 30 min of cycling exercise was significantly different in men with type 2 diabetes compared with those with normal glucose tolerance. Specifically, men with diabetes demonstrated enrichment of genes associated with inflammation and ECM remodeling, and reduced expression of genes associated with metabolic control (61). These data are consistent with data from our laboratory and others demonstrating an altered inflammatory and ECM remodeling signatures in muscle from rodent models of low exercise response and impaired glucose tolerance in response to exercise (23,62).…”
Section: Altered Exercise-induced Gene Expression In Skeletal Musclementioning
confidence: 99%